2003
DOI: 10.1093/hmg/ddg316
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin germline missense mutations and cell phenotype: evidence for the independence of cell invasion on the motile capabilities of the cells

Abstract: In Hereditary Diffuse Gastric Cancer syndrome, E-cadherin germline mutations of the missense type harbour significant functional consequences. In this study, we have characterised the effect of T340A, A617T, A634V and V832M E-cadherin germline missense mutations on cell morphology, motility and proliferation. Wild-type E-cadherin and A617T expressing cells have an epithelial-like morphology, with polarised cells migrating unidirectionally. T340A and A634V expressing cells, fibroblast-like, have a high motile p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 51 publications
6
97
2
1
Order By: Relevance
“…21,47 Surprisingly, the mutant V832M, which was described to interact normally with b-catenin but not with a-catenin, 36,48 shows decreased association with b-catenin. This can be due to the increased sensibility and accuracy of PLA to detect protein-protein interactions when compared with co-immunoprecipitation technique.…”
Section: Cdh1 Missense Mutations Affect E-cadherin Subcellular Localimentioning
confidence: 99%
See 3 more Smart Citations
“…21,47 Surprisingly, the mutant V832M, which was described to interact normally with b-catenin but not with a-catenin, 36,48 shows decreased association with b-catenin. This can be due to the increased sensibility and accuracy of PLA to detect protein-protein interactions when compared with co-immunoprecipitation technique.…”
Section: Cdh1 Missense Mutations Affect E-cadherin Subcellular Localimentioning
confidence: 99%
“…E-cadherin mutants T340A, A634V, R749W, E757K, E781D, P799R and V832M found in the HDGC context, 16,18,19,21,[34][35][36][37][38] were constructed by site-directed mutagenesis in the entry vector CDH1pENTR 221 (Clone ID: IOH46767, Invitrogen, Grand Island, NY, USA), following the protocol described by Wang and Wilkinson. 41 By LR recombination reaction, the open reading frame was subcloned in the pEF6/Myc-His vector (Invitrogen).…”
Section: Plasmids Constructionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10] However, previous studies have reported that none of the studied germline E-cadherin mutations is responsible for an increase in the b-catenin/Lef transcriptional activity. 11,12 E-Cadherin Cytoplasmic Domain Induces Cyclin D1, AP-1 and STAT1/STAT2 Promoter Activities…”
Section: Correlation Of Nuclear E-cadherin Accumulation With Nuclear mentioning
confidence: 99%